Homo Viator: Human Beings as Pilgrims Driven by Hope - Heribertus Dwi Kristanto (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
The Jubilee Year of Hope, in which many Christians make a pilgrimage to pass through the Holy Door, is an opportune moment to reflect on the relationship between the existential fact of human as homo viator and hope as a virtue that should animate him/her. While in the Christian tradition hope is clearly considered one of the theological virtues, some prominent philosophers have expressed a negative view of hope, arguing that hope promotes passivity and does not lead to action. Christian hope, anchored in the expectation of heavenly bliss, is accused of being a kind of escapism. Through a literary study of several classical and contemporary thinkers, such as Thomas Aquinas, Gabriel Marcel, Victor Frankl, Josef Pieper, and Byung-Chul Han, this paper argues that hope as a passion is indeed ambivalent, insofar as people can hope that evil befall on another. As a theological virtue, however, hope opens the human horizon to future possibility and transcendence, in that hope not only sustains the human spirit in the face of adversities, but also, and more importantly, gives meaning to the human journey on earth. By keeping despair at bay, hope enables man to say “yes” to arduous life and generates forces that move him/her to action.